Analisis Pemahaman Konsep Siswa Kelas IX SMP Negeri 1 Sigi pada Materi Lingkaran Ditinjau dari Kemampuan Matematika - Indri Riskiyana; Nurhayadi Nurhayadi; I Nyoman Murdiana; Tegoeh S. Karniman (Universitas Tadulako, 2026)
This study aims to obtain a description of the Concept Understanding of Students in class IX SMP Negeri 1 Sigi on circle material in terms of math ability. This type of research is qualitative research with descriptive approach. The subjects of this study are three students of class IX SMP Negeri 1 Sigi in the odd semester 2024/2025 consisting of 1 student with high mathematics ability, 1 student with moderate mathematics ability, and 1 student with low mathematics ability. Subjects are selected based on report card scores and subject teacher recommendations. Data were obtained from the results of written tests and interviews with research subjects. The data credibility was tested through membercheck. The results of the study indicate that, (1) Subjects with high mathematical ability (ST) meet 3 indicators of concept understanding, namely restating the concepts that have been learned, identifying examples and non-examples of concepts that have been learned, and applying concepts or algorithms to solve a problem. (2) Subjects with moderate mathematical ability (SS) meet 3 indicators of concept comprehension, namely restating concepts that have been learned, identifying examples and non-examples of concepts that have been learned, and applying concepts or algorithms to solve a problem. (3) Subjects with low mathematical ability (SR) only meet 1 indicator of concept understanding, namely identifying examples and not examples of the concepts that have been studied.